2020
DOI: 10.52571/ptq.v17.n35.2020.22_iztayev_pgs_239_258.pdf
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies of the Baisheshek Barley Grain Processed by the Ion-Ozone Mixture

Abstract: The article presents the results of an experimental study of Baisheshek barley grain treated with an ion ozone mixture. This study aims to develop an innovative technology for processing barley with an ion-ozone mixture in order to increase their technological parameters, yield, quality, and grain safety. Kazakhstan has sharply increased the export of barley, and all agronomists, producers, and breeders are actively moving to the cultivation of this crop, while increasing production, productivity, improving pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…However, as a rule, the elements of technology in these conditions significantly affect the productivity of any crop. Improperly chosen technology parameters can lead to the development of low productivity of safflower sowings, which, consequently, will affect the yield of oilseeds (Roche et al, 2019;Salvatore et al, 2019;Iztaev et al, 2020). The conducted research revealed that the best parameters of the elements of yield structure and safflower productivity are established in the application of the biologized cultivation technology.…”
Section: Resultsmentioning
confidence: 99%
“…However, as a rule, the elements of technology in these conditions significantly affect the productivity of any crop. Improperly chosen technology parameters can lead to the development of low productivity of safflower sowings, which, consequently, will affect the yield of oilseeds (Roche et al, 2019;Salvatore et al, 2019;Iztaev et al, 2020). The conducted research revealed that the best parameters of the elements of yield structure and safflower productivity are established in the application of the biologized cultivation technology.…”
Section: Resultsmentioning
confidence: 99%
“…It is therefore, in the first approximation, we chose coarse wheat grit № 1 with humidity of 12,1 % as an object of research. Typical curves of wheatgrass density dependence on compression pressure, shown in Figure 6, have the form of exponents, and we can see that as the pressure of compression increases, the density of the material increases 4 .…”
Section: Fig 4 Dependence Of Absolute Deformation Of Wheat Grain On C...mentioning
confidence: 92%
“…As can be seen from the data presented in Figure 1, the sprouted grain has a more significant mass fraction of water [31] than the original non-sprouted grain but slightly lower indicators [32] in terms of the mass fraction of protein, carbohydrates, and lipids compared to the original grain [33]. This property of sprouted grain is because these substances are spent on the processes associated with the formation and development of the plant embryo [34]. At the same time, there is a large amount of various vitamins in sprouted grains, often exceeding the amount of vitamins in non-sprouted grains (Figure 6).…”
Section: Figure 5 Comparative Indicators Of the Original And Sprouted...mentioning
confidence: 94%